Preliminary study of the enzyme ubiquitin carboxylterminal hydrolase 14 (UBP6) in Giardia intestinalis: structural bioinformatic analysis and transcriptional profile during encystation (2014)
This paper presents a combined approachwith two aims. The first is to analyze thereported sequence of the enzyme ubiquitincarboxyl-terminal hydrolase 14 of Giardiaintestinalis (UBP6) through computationalmethods to find components related withits hypothetical function. The second isto determine if the protein-coding gene isexpressed in G. intestinalis and, if such isthe case, also determine its transcriptionpattern along the life cycle of the parasite. Itwas established that the protein belongs tothe family of Cys-dependent deubiquitinasesand more specifically to ubiquitin specificproteases (USPs). Moreover, the catalyticcenter with the complete triad as well astypical features of the USP motif were alsoidentified. Since the computational findingssuggest that the enzyme could be functional,reverse transcription coupled to PCR wasused as a first approach to establish if in factthe coding gene is expressed in the parasite.Interestingly, it was found not only thatthe gene is expressed, but also that thereis a transcription variation along the lifecycle of the parasite. These two findings arethe starting point for further studies sincethey tentatively suggest that this enzymecould be involved in the protein turnoverthat occurs during parasite encystation.Although preliminary, this study is the firstreport concerning the study of a specificdeubiquitinating enzyme in the parasite G.intestinalis.